Relationship between Knowledge and Mother's Attitude About Clean and Healthy Living on the Incidence of Diarrhea in Toddlers in Perlis Village, Brandan District - Tri Suci Dewi Wati; Dwi Sumidawati (Science Midwifery, 2019)
Diarrhea is the leading cause of death for children under five years old, diarrhea kills around 760,000 children under five every year and globally there are nearly 1.7 billion diarrheal diseases each year. The type of research used is descriptive correlation with a cross sectional approach to determine the relationship between knowledge and attitudes of mothers about clean and healthy living on the incidence of diarrhea in the elderly. The population in this study were all mothers who had children under five (1-5 years old) who suffered from diarrhea in the village of Brandan Timur Baru as many as 30 people. The sampling technique used a total sampling of 30 people. The results of statistical tests obtained that there was a relationship between knowledge about clean and healthy living on the incidence of diarrhea in children under five, with a degree of significance (α) = 0, 05 and df = 2, the calculation results are Sig (2-tailed) 0.032 < (α) = 0.05, there is a relationship between attitudes about clean living on the incidence of diarrhea in toddlers with the degree of significance (α) = 0.05 and df = 1, the calculation result is Sig (2-tailed) 0.007 < (α) = 0.05. Mother's knowledge can be increased through an intensive approach to the problem of diarrheal disease by providing counseling on clean and healthy living.